Ensuring equal opportunity: Gender equality in workplace - Farsia, Lina (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2024)
Gender discrimination in the workplace remains a significant challenge, affecting various aspects of employment, including hiring, promotion, and compensation. Despite advancements in gender equality, women are often treated less favorably than men, irrespective of their qualifications and performance. This issue is pervasive and can be influenced by deeply rooted cultural and religious beliefs that shape attitudes and decisions in professional settings. Women frequently face barriers to leadership roles and receive lower wages compared to their male counterparts. This paper explores the ongoing gender discrimination in workplaces, highlighting its causes and impacts, and proposes actionable strategies to foster a more inclusive and equitable work environment for all employees.